2022
DOI: 10.1155/2022/8660965
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA LINC00909 Induces Epithelial-Mesenchymal Transition and Contributes to Osteosarcoma Tumorigenesis and Metastasis

Abstract: Background. Osteosarcoma (OS) is a malignant tumor that is highly metastatic with a high mortality rate. Although mounting evidence suggests that LINC00909 is strongly associated with the malignant progression of various tumors, the exact role of LINC00909 in OS remains unknown. Therefore, the current study was designed to investigate the relationship between LINC00909 and the malignant progression of OS. Methods. LINC00909 expression was measured in OS cell lines and clinical specimens using RT-qPCR assays. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Consistent with its overexpression in osteosarcoma samples, LINC01060 knockdown in osteosarcoma cells considerably inhibited cell proliferation, enhanced cell apoptosis, and elicited G1-phase arrest of the cell cycle. In addition, EMT enables osteosarcoma cells to invade and metastasize during the malignant progression of osteosarcoma 38 . Regarding EMT, LINC01060 knockdown decreased the protein contents of N-cadherin and Vimentin as mesenchymal cell factors, whereas it increased the content of E-cadherin as an epithelial marker 4 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with its overexpression in osteosarcoma samples, LINC01060 knockdown in osteosarcoma cells considerably inhibited cell proliferation, enhanced cell apoptosis, and elicited G1-phase arrest of the cell cycle. In addition, EMT enables osteosarcoma cells to invade and metastasize during the malignant progression of osteosarcoma 38 . Regarding EMT, LINC01060 knockdown decreased the protein contents of N-cadherin and Vimentin as mesenchymal cell factors, whereas it increased the content of E-cadherin as an epithelial marker 4 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…promotes the migration and invasion of osteosarcoma cells by upregulating the expression of TERT and TERC, which subsequently activates the Wnt/β-catenin signaling pathway. 36 Furthermore, LINC00909 was found to interact with RNA-binding protein HuR to stabilize TERT and TERC mRNA, which contributes to the sustained expression of TERT and TERC in osteosarcoma cells. 27 Besides the canonical processing of TERC, terc-sRNA has been identified that is upregulated in different tumors and can increase telomerase activity.…”
Section: Tert Regulation Of Vegf Expressionmentioning
confidence: 99%
“…One study found that the long noncoding RNA (lncRNA) LINC00909 induces EMT and contributes to osteosarcoma tumorigenesis and metastasis. The study revealed that LINC00909 promotes the migration and invasion of osteosarcoma cells by upregulating the expression of TERT and TERC, which subsequently activates the Wnt/β‐catenin signaling pathway 36 . Furthermore, LINC00909 was found to interact with RNA‐binding protein HuR to stabilize TERT and TERC mRNA, which contributes to the sustained expression of TERT and TERC in osteosarcoma cells 27 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PI3K/AKT pathway has been confirmed to play a key role in dedifferentiation and tumor cell growth in ATC [29]. Previous research suggested that HOXD9 could influence the progression of osteosarcoma malignancy via the PI3K/AKT/mTOR pathway [43]. Through the modulation of the PI3K/AKT/mTOR pathway, miR-451a has the potential to operate as a tumor suppressor in patients with gastric cancer [44].…”
Section: Table 4 Correlations Between Psmb8 Protein Expression With C...mentioning
confidence: 99%